Underpricing on the selected European Alternative Investment Markets - Dominika Hadro; Marek Pauka (e-Finanse: Financial Internet Quarterly, 2019)
The phenomenon of underpricing is the subject of many studies on the stock markets, but there is still a research gap referring to the European Alternative Investment Markets, markets for small and medium companies. They are a source of capital and such an anomaly as underpricing could be a barrier for development of young companies. It means so-called money left on the table, which constrain the effectiveness of the market. The purpose of the paper is to analyze whether lower entry regulations on the European Alternative Investment Markets are correlated with the higher value of underpricing as the demonstration of higher investing risk. We calculate raw initial returns with different equilibrium prices for three European Alternative Investment Markets and confirm that NewConnect, the market with the lighter legal environment, has the highest initial returns for the first day of trading, however after one month returns turn out to be significantly lower than on the other two markets and differs for aftermarket rate of returns. Our results suggest that there is a premium for higher risk on NewConnect, but only after one month rate of returns turn out to be negative, which can suggest that market participants verify very quickly the quality of issuers.
Keywords: G12; G14; 330; underpricing; alternative investment market; IPO